HUBUNGAN PENGETAHUAN IBU TENTANG STIMULASI DINI DENGAN PERKEMBANGAN MOTORIK PADA ANAK USIA 6-24 BULAN DI KECAMATAN MAYANG KABUPATEN JEMBER - Kusuma, Irawan Fajar; Syamlan, Ramzi; Yoniko, Ayu (IKESMA, 2013)
More than two third of toddler in some developing countries suffer from declining of their childhood development. In Indonesia, in 2003, Department of Health has conducted childhood development in 30 provinces and reported that 45,12 % of infant has suffered from growth and development disorder. One of factors that influence the development is early stimulation especially from people close to the toddler (mother and other family).The aim of this study is to analyze the relationship between motherâs knowledge about early stimulation and motoric development of toddlers. This is an observational study of case control design. To obtain the samples, the technique is non probability sampling with consecutive sampling. Motoric development of toddlers from 6 â 24 month old are observed by KPSP form. Data are analyzed using bivariate analysis of Marginal Homogeneity test and Conditional Regressiona Logistic (Confidence Interval 95%). The result shows that motherâs knowledge on early stimulation have significant effect to the motoric development of toddlers. The odds ratio shows 4,950 means that the lack of knowledge of the mother on early stimulation may increase the risk of motoric development disorder about nearly 5 times. It can be conclude that there is significant relationship between motherâs knowledge on early stimulation and motoric development disorder. Mother who is in the closest position of toddlers should be educated with this knowledge of education.